PENGEMBANGAN MODEL SENAM BERBASIS PENCAK SILAT - Widiastuti Widiastuti; Ira Fhitriani (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2017)
Abstract :The purpose of research and development of learning model of pencak silat gymnastics for elementary school students. This research and development model is conducted to improve the creativity of physical education teachers in presenting learning materials. This research and development uses Research & Development (R & D) research method from Borg and Gall. Test the effectiveness of the model using the instrument of Physical Freshness Tests Indonesia (TKJI). Analysis of research data using t test with significance 0.05 analysis data obtained value average (Pretest): 13.17 and (Posttest): 16.03 with significance value: 0.00 <0.05 with significance 0.05 then Ho rejected. Based on the information, it can be concluded that the learning model of pencak silat (IF) for elementary school pupils developed can be applied effectively and efficiently so as to improve students' physical fitness. Abstrak : Tujuan penelitian dan pengembangan model pembelajaran senam pencak silat untuk murid Sekolah Dasar. Model penelitian dan pengembangan ini dilakukan untuk meningkatkan kreatifitas guru pendidikan jasmani dalam menyajikan materi pembelajaran pencak silat. Penelitian dan pengembangan ini menggunakan metode penelitian pengembangan Resecarch & Development (R & D) dari Borg and Gall. Uji efektifitas model menggunakan instrument Tes Kesegaran Jasmani Indonesia (TKJI). Analisis data penelitian menggunakan uji t dengan taraf signifikansi 0.05 analisis data diperoleh nilai rata-rata (Pretest): 13.17 dan (Posttest): 16.03 dengan nilai signifikasi: 0.00 <0.05 dengan tariff signifikasi 0.05 maka Ho ditolak. Berdasarkan keterangan tersebut dapat disimpulkan bahwa model pembelajaran senam berbasis pencak silat untuk murid Sekolah Dasar yang dikembangkan dapat di aplikasikan secara efektif dan efesien sehingga dapat meningkatkan kesegaran jasmani siswa. Kata kunci : Model pembelajaran, senam, penca silat